Activity of Pazopanib and Trabectedin in Advanced Alveolar Soft Part Sarcoma. (28th July 2017) - Stacchiotti, Silvia; Mir, Olivier; Le Cesne, Axel; Vincenzi, Bruno; Fedenko, Alexander; Maki, Robert G.; Somaiah, Neeta; Patel, Shreyaskumar; Brahmi, Mehedi; Blay, Jean Y.; Boye, Kjetil; Sundby Hall, Kirsten; et al.
Abstract : Background: Alveolar soft part sarcoma (ASPS) is an exceedingly rare and orphan disease, without active drugs approved in the front line. Pazopanib and trabectedin are licensed for sarcoma treatment from second‐line, but very little and contradictory data are available on their activity in ASPS. Lacking ongoing and/or planned clinical trials, we conducted a multi‐institutional study involving the reference sites for sarcoma in Europe, U.S., and Japan, within the World Sarcoma Network, to investigate the efficacy of pazopanib and trabectedin. Materials and Methods: From May 2007, 14 of the 27 centers that were asked to retrospectively review their databases had identified 44 advanced ASPS patients treated with pazopanib and/or trabectedin. Response was evaluated by Response Evaluation Criteria in Solid Tumors 1.1. Progression‐free survival (PFS) and overall survival (OS) were computed by Kaplan‐Meier method. Results: Among 30 patients who received pazopanib, 18 were pretreated (13 with other antiangiogenics). Response was evaluable in 29/30 patients. Best responses were 1 complete response, 7 partial response (PR), 17 stable disease (SD), and 4 progressions. At a 19‐month median follow‐up, median PFS was 13.6 months (range: 1.6–32.2+), with 59% of patients progression‐free at 1 year. Median OS was not reached. Among 23 patients treated with trabectedin, all were pretreated and evaluable for response. Best responses were 1 PR, 13 SD, and 9 progressions. At a 27‐month median follow‐up, median PFS was 3.7 months (range: 0.7–109), with 13% of patients progression‐free at 1 year. Median OS was 9.1 months. Conclusion: The value of pazopanib in advanced ASPS is confirmed, with durable responses, whereas the value of trabectedin appears limited. These results are relevant to defining the best approach to advanced ASPS. Implications for Practice: This retrospective study, conducted among the world reference centers for treatment of sarcoma, confirms the value of pazopanib in patients with advanced alveolar soft part sarcoma (ASPS), with dimensional and durable responses, whereas trabectedin shows a limited activity. Alveolar soft part sarcoma is resistant to conventional cytotoxic chemotherapy. Pazopanib and trabectedin are licensed for treatment of sarcoma from second line; in the lack of prospective clinical trials, these results are relevant to defining ASPS best management and strongly support initiatives aimed at obtaining the approval of pazopanib in the front line of the disease. Abstract : Because of the rarity of alveolar soft part sarcoma and the lack of prospective trials, a retrospective, multi‐institutional, caseseries analysis was conducted among reference centers for treatment of soft tissue sarcoma.With the support of the World Sarcoma Network, the activity and efficacy of trabectedin and pazopanib in advanced alveolar soft part sarcoma patients was investigated. The results are presented here.